1985
DOI: 10.1111/j.1532-5415.1985.tb06316.x
|View full text |Cite
|
Sign up to set email alerts
|

Community‐Based Geriatric Assessment

Abstract: A comprehensive review of the multidisciplinary functional assessment and treatment of 800 patients seen at a community-based geriatric assessment center was performed to profile clinical characteristics of patients attending such a program and to evaluate possible predictors of institutionalization. The most common problems addressed were senile dementia (46%), hypertension (31%), clinically significant depression (30%), and burdened caregiver (24%). More than 90% of patients were able to remain in the commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…The importance of supporting carers is stressed continually, yet there is little evidence of skill sharing and support in the management of dementia patients at home. It has been reported elsewhere (Martin et a/. 1985, Scott & Wenger 1994) that the admission rate to residential services is high for those suffering from dementia.…”
Section: Implications For Community Carementioning
confidence: 93%
See 2 more Smart Citations
“…The importance of supporting carers is stressed continually, yet there is little evidence of skill sharing and support in the management of dementia patients at home. It has been reported elsewhere (Martin et a/. 1985, Scott & Wenger 1994) that the admission rate to residential services is high for those suffering from dementia.…”
Section: Implications For Community Carementioning
confidence: 93%
“…1985, Scott & Wenger 1994) that the admission rate to residential services is high for those suffering from dementia. It has been suggested that adequate formal help and psychological support for primary caregivers delays institutionalization (Brane 1986, Martin et al 1985. It has also been shown that initial effective interventions in the community are beneficid to carers over time despite declining functioning of the dementia sufferer (Pynoos & Ohta 1991).…”
Section: Implications For Community Carementioning
confidence: 99%
See 1 more Smart Citation
“…Numerous investigators have questioned the wisdom of multiple drug use in the elderly because it results in iatrogenic illness, drug-drug interactions, and decreased medication compliance. [6][7][8] Although warnings concerning the use of multiple medications in the elderly are sounded frequently, pressures to prescribe even more drugs will continue in the future. This is expected because research will enhance the physician's ability to identify diseases in the elderly and expand the physician's armamentarium of therapeutic modalities.…”
mentioning
confidence: 99%
“…Treating Multi‐Problem Patients Requiring Several Disciplines Although the concept of the multidisciplinary team has gained wide acceptance, the effects of team care have been difficult to separate from the effects of the assessment process 11,19–24 . Such teams can operate in inpatient, ambulatory, home health, or long‐term care settings.…”
Section: Discussionmentioning
confidence: 99%